Pembingkaian Narasi Media Massa Terkait Dugaan Manipulasi Pemilu 2024 - Nabilah Azzahra; Filia (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2024)
This study aims to analyze the framing of mass media narratives regarding the alleged manipulation of the 2024 Election, revealed through the research data source, namely the documentary film Dirty Vote and the TV program Bocor Alus Politik titled “Hak Angket Kecurangan Pemilu VS Tawaran Kursi Menteri Prabowo-Gibran” and "Cerita Di Balik Pemilu Satu Putaran”. The research is drawn from the narrative quotes provided by sources in both media. The methodology used is Robert N. Entman’s framing analysis with a qualitative approach, along with Fairclough’s critical discourse analysis model. The analysis technique involves identifying framing categories, including problem identification, casual interpretation, moral evaluation, and treatment recommendation. The results indicate that both media frame the 2024 Election as an event full of fraud and organized manipulation. The emerging narrative emphasizes the need for public awareness and decisive actions by law enforcement to maintain the integrity of democracy. Additionally, both media criticize political manipulation that undermines the democratic process and suggest that the audience should have a higher awareness when choosing leaders.